2010
DOI: 10.1007/s11548-010-0492-x
|View full text |Cite
|
Sign up to set email alerts
|

Regional image analysis of the tongue color spectrum

Abstract: Using a hyperspectral camera and extraction algorithm, the tongue color of the uncoated part was automatically extracted. This technique is suitable for tongue color analysis and may help non-trained users to identify "Mibyou".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 18 publications
(27 reference statements)
1
27
0
Order By: Relevance
“…The hyperspectral imaging system, one of the objective measurement systems available, will help even lesser-trained people to perform this diagnosis of Kampo medicine. However, because a hyperspectral camera presents a major problem in terms of cost [3,Discussion], it is thought that tongue color spectra can be estimated from 3-band images as shown in skin images [11]. If a hyperspectral camera is replaced with a 3-band CCD camera and spectral property of the tongue is estimated for 3-band images, this system would be a new, easily applied, low-cost and noninvasive diagnostic tool for preventive medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperspectral imaging system, one of the objective measurement systems available, will help even lesser-trained people to perform this diagnosis of Kampo medicine. However, because a hyperspectral camera presents a major problem in terms of cost [3,Discussion], it is thought that tongue color spectra can be estimated from 3-band images as shown in skin images [11]. If a hyperspectral camera is replaced with a 3-band CCD camera and spectral property of the tongue is estimated for 3-band images, this system would be a new, easily applied, low-cost and noninvasive diagnostic tool for preventive medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the problems Kampo is facing are discussed in the first article [3,Introduction]. Also, we showed that uncoated tongue area can be segmented properly by focusing on spectral color difference among facial areas, which will help analyze tongue color without the effect of tongue coating.…”
Section: Introductionmentioning
confidence: 92%
“…Many categories are not precise enough, but more like estimation, i.e. the judgment whether a tongue is purplish the tongue images within our device is still not standardized in that respect, that the subjective analysis of the examiner is replaced by a computer that quantitatively analyzes the images, as tried to establish by other research groups [26][27][28][29][30]. The complete standardization of tongue imaging with a standardized recording procedure as well as integrated quantitative analysis of the tongue by means of a computer could be a goal for the future.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with ubiquitous application of advanced computer technologies in medical science, we cannot ignore new possibilities to improve TCM with computer technologies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]; these possibilities for improvement have drawn attention from myriads of researchers. Chiu [4,5] built a computerized tongue examination system (CTES) based on computerized image analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Before the process of tongue classification, an exact region of the tongue must be extracted from an image, [12][13] try to proposed automated tongue segmentation method. Some papers [14][15][16][17][18] designed image analysis system for feature extraction and diagnostics. Pang et al [18] even present a tongue-computing model for the diagnosis of appendicitis based on quantitative measurements that include chromatic and textural feature.…”
Section: Introductionmentioning
confidence: 99%